2023
DOI: 10.1029/2023ms003757
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning of Systematic Sea Ice Model Errors From Data Assimilation Increments

William Gregory,
Mitchell Bushuk,
Alistair Adcroft
et al.

Abstract: Data assimilation is often viewed as a framework for correcting short‐term error growth in dynamical climate model forecasts. When viewed on the time scales of climate however, these short‐term corrections, or analysis increments, can closely mirror the systematic bias patterns of the dynamical model. In this study, we use convolutional neural networks (CNNs) to learn a mapping from model state variables to analysis increments, in order to showcase the feasibility of a data‐driven model parameterization which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 98 publications
(151 reference statements)
0
9
0
Order By: Relevance
“…Convolutional neural networks (CNNs) have been used to predict parameterizations of ocean momentum backscatter in a variety of models (Bolton & Zanna, 2019;Guillaumin & Zanna, 2021;Zanna & Bolton, 2020) and have been implemented in an ocean primitive equation model (Zhang et al, 2023). Gregory et al (2023) recently employed CNNs to learn data assimilation increments for sea-ice and showed that networks could be used to reduce biases in sea-ice.…”
Section: Machine Learning Is An Emerging Tool To Improve Ogcmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Convolutional neural networks (CNNs) have been used to predict parameterizations of ocean momentum backscatter in a variety of models (Bolton & Zanna, 2019;Guillaumin & Zanna, 2021;Zanna & Bolton, 2020) and have been implemented in an ocean primitive equation model (Zhang et al, 2023). Gregory et al (2023) recently employed CNNs to learn data assimilation increments for sea-ice and showed that networks could be used to reduce biases in sea-ice.…”
Section: Machine Learning Is An Emerging Tool To Improve Ogcmsmentioning
confidence: 99%
“…Gregory et al. (2023) recently employed CNNs to learn data assimilation increments for sea‐ice and showed that networks could be used to reduce biases in sea‐ice.…”
Section: Introductionmentioning
confidence: 99%
“…Readers are also referred to Bocquet et al (2020) and Brajard et al (2020) for seminal works in this field. In a recent sea ice study by Gregory et al (2023), hereafter G23, the authors presented a DA-based ML framework in which convolutional neural networks (CNNs) were used to predict state-dependent sea ice errors within an ice-ocean configuration of the Geophysical Fluid Dynamics Laboratory (GFDL) Seamless system for Prediction and EArth System Research (SPEAR) model, as a way to highlight the feasibility of a data-driven sea ice model parameterization within SPEAR. They approached this by first showing that the climatological sea ice concentration analysis increments from an ice-ocean DA experiment map closely onto the systematic bias patterns of the equivalent free-running model.…”
Section: Introductionmentioning
confidence: 99%
“…
In this study, we perform online sea ice bias correction within a Geophysical Fluid Dynamics Laboratory global ice-ocean model. For this, we use a convolutional neural network (CNN) which was developed in a previous study (Gregory et al, 2023, https://doi.org/10.1029/2023ms003757) for the purpose of predicting sea ice concentration (SIC) data assimilation (DA) increments. An initial implementation of the CNN shows systematic improvements in SIC biases relative to the free-running model, however large summertime errors remain.
…”
mentioning
confidence: 99%
“…A number of recent studies have followed this approach and used ML to learn the model errors, showing promising results in various systems, from simple toy models to NWP models (Arcomano et al, 2023;Bora et al, 2023;Bretherton et al, 2022;Carrassi & Vannitsem, 2011;N. Chen & Zhang, 2023;T.-C. Chen et al, 2022;Clark et al, 2022;Farchi et al, 2021;Gregory et al, 2023;Mojgani et al, 2022;Mitchell & Carrassi, 2015;Lang et al, 2016;Pawar et al, 2020;Pathak et al, 2020;Watson, 2019;Watt-Meyer et al, 2021;Yuval et al, 2021). However, most of these studies have directly learned the model error using deep artificial neural networks (ANNs): ANNs are trained using many pairs of state and analysis increments from a training set.…”
Section: Introductionmentioning
confidence: 99%